Dampak CSR PT Bank Rakyat Indonesia (PERSERO) Terhadap Pembiayaan UMKM di Indonesia - Cicilia Jovana Arlinaninova; Dewi , Preditha Kinanti (Universitas 17 Agustus 1945 Semarang, 2024)
This study analyzes the impact of Corporate Social Responsibility (CSR) initiatives by PT Bank Rakyat Indonesia (Persero) on the development of Micro, Small and Medium Enterprises (MSMEs) in Indonesia by 2024. Using a qualitative research approach with in-depth interviews and direct participatory observation of MSME stakeholders who benefit from BRI's CSR programs, the study reveals significant positive results. CSR interventions not only enhance the capacity and competitiveness of MSMEs but also improve their access to financing. Furthermore, the research highlights the broader social and environmental impacts of BRI's CSR, confirming its role in encouraging sustainable business practices among MSMEs. The research findings show strong synergies between BRI's CSR efforts and local government support, which enhances the program's effectiveness and reach across different regions of Indonesia. This research underscores the critical role of CSR in driving inclusive economic development and sustainable growth in Indonesia, advocating for continued support and refinement of CSR strategies as a key driver of economic empowerment and environmental stewardship.